Blended Learning in Higher Education: Diversifying Models and Practical Recommendations for Researchers - Platonova, Raisa I.; Orekhovskaya, Natalia A.; Dautova, Saule B.; Martynenko, Elena V.; Kryukova, Nina I.; Demir, Servet (Frontiers in Education, 2022)
Blended learning is gaining popularity because it has shown to be a successful method for accommodating an increasingly varied student body, while enhancing the learning environment by incorporating online teaching materials. Higher education research on blended learning contributes to the blended learning literature. The ideas for future researchers are a vital component of research-based research articles. This study aims to consolidate the recommendations made to future studies. In this regard, research articles published in Scope-indexed journals during the past five years have been analyzed. In this analysis, each of the quoted passages from the research were independently read and coded. Following a period of time, the codes were amalgamated to form categories and themes. In the section on results, direct quotations were used to substantiate the encodings. The number of publications increased starting in 2017 and continuing through 2020. In the year 2020, the most articles were published. Approximately half of the publications provide recommendations for future research. Under the titles "Research Content" and "Replication and Method" the researchers' recommendations were gathered.